2008
DOI: 10.2214/ajr.07.2835
|View full text |Cite
|
Sign up to set email alerts
|

Atrophy and Fatty Infiltration of the Supraspinatus Muscle: Sonography Versus MRI

Abstract: Our study suggests that there is a good correlation between sonography and MRI for the assessment of supraspinatus muscle atrophy and fatty infiltration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
121
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(128 citation statements)
references
References 30 publications
3
121
2
2
Order By: Relevance
“…The use of static ultrasonography images for the muscle evaluations may explain the relatively low accuracy in that study. In contrast, Khoury et al 9 evaluated the cuff muscles in real time as we did, with a technique similar to ours, and demonstrated an accuracy comparable with that in the present study.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The use of static ultrasonography images for the muscle evaluations may explain the relatively low accuracy in that study. In contrast, Khoury et al 9 evaluated the cuff muscles in real time as we did, with a technique similar to ours, and demonstrated an accuracy comparable with that in the present study.…”
Section: Discussionsupporting
confidence: 80%
“…In that study, the mean weighted kappa value was 0.45 for both the supraspinatus and infraspinatus muscles. Although the original Goutallier grading system was based on axial CT images 12 and the agreement between CT and MRI was not satisfactory, MRI has become the accepted modality for the diagnosis and grading of fatty degeneration 9,10 . The agreement between ultrasonography and MRI in the present study was better than the reported agreement between CT and MRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound is an alternative assessment modality that is cheaper, less time consuming, and has greater availability at some institutions, although it is technician dependent. In a study of 45 shoulders from 39 patients, high comparability in the accuracy of MRI and ultrasound was suggested, with a reported correlation coefficient of 0.90 (21). Ultrasound had 94.4% sensitivity and 91.3% specificity in diagnosing supraspinatus FI, with lower levels for the infraspinatus.…”
Section: Significance and Innovationsmentioning
confidence: 98%
“…We considered that the tangent sign was absent when the superior margin of the supraspinatus muscle was superior to the line tangential to the coracoid and scapular spine (9,10). Occupation ratio was measured according to the method described by Thomazeau et al (11) and Khoury et al (12), which was the ratio between the cross section of the supraspinatus muscle belly and that of its fossa on the T1-weighted oblique sagittal image crossing through the medial border of the coracoid process of the scapula. Lines were drawn as close as possible to the supraspinatus outer margin, inner margins of the coracoid process and scapular spine, and superior limits of the supraspinatus fossa.…”
Section: Imaging Interpretationmentioning
confidence: 99%